Vilnius as the Center of the Belarusian National Movement in the First Half of the 20th Century - Figura, Marek (Sensus Historiae, 2025)
In the first half of the 20th century, Vilnius, the capital of the former Grand Duchy of Belarus, played a key role not only in the history of Lithuanians and Poles, but also of Belarusians. The traditions of the Belarusian presence in Vilnius date back to the Middle Ages, when the then Orthodox Ruthenians, the progenitors of later Belarusians, lived there. This presence is clearly evidenced by the impressive Orthodox and Uniate temples which, alongside numerous Catholic churches, as well as Jewish, Muslim and Protestant temples, confirmed the multi-religious and multi-cultural character of Vilnius. The city was also very important for the development of Belarusian culture and Belarusian national revival. It was there that one of the main centers of the Belarusian national movement was located, and it was in Vilnius that Belarusian institutions and organizations were established and operated, led by the weekly “Nasha Niva” (1906–1915), which was key to this process. It is there where the actual center of Belarusian cultural and political life was located until the revolution in the Russian Empire; only after this event would this role be played by Minsk, where in the spring of 1918 the Belarusian People’s Republic would be proclaimed. But even then, many Belarusians considered Vilnius to be the second Belarusian capital, next to Minsk, especially when it comes to culture. Also later, in the turbulent years 1918–1922, when the political affiliation of the city fought over by Lithuanians, Poles and Bolsheviks changed many times, Vilnius was an important center for Belarusians looking for opportunities to develop national culture and education. After 1920, Vilnius would become an important center for those Belarusians who were critical of the policy of Soviet Belarus and hoped that Poland would support the Belarusian issue. After the incorporation of the Vilnius region into the Second Polish Republic at the beginning of 1922, disappointment with Polish policy towards Belarusians quickly followed, but then, next to Belarusian cultural and educational institutions, the Belarusian press and Belarusian politicians, including Belarusian MPs and senators elected from the national minority bloc list, would be visible in Vilnius. The lack of agricultural reforms and restrictions on Belarusian education resulted in the growing radicalization of Belarusian politicians. Due to the policy of Belarusianization pursued in the BSSR at that time, many of them switched to communist positions, which resulted in repression by the Polish authorities. The latter will intensify in the 1930s, when, on the one hand, there will be a retreat from the Koreanization policy in the USSR, and on the other hand, Sanation Poland will become an increasingly authoritarian state. Despite these limitations, Vilnius will remain an important center of Belarusian culture until the end of the Second Polish Republic, and its role will become even more important the more Stalinist repression in the BSSR intensifies.